(untitled) (Confluenţe Bibliologice, 2024)
The article highlights the professional activity of bibliographer Elena Scurtu (née Grama), a distinguished personality who devoted the most meaningful years of her life to serving the book and the library with faith and passion. She worked in the field for over half a century. Her rich professional experience in the field of bibliology places her among the distinguished librarians who have contributed significantly to the history of the USARB Scientific Library.